PEMBINAAN SOFT SKILL GURU MELALUI KEGIATAN HALAQOH UNTUK SUKSESI PPA DI SD AL-IRSYAD AL-ISLAMIYYAH PURWOKERTO - Novan Ardy Wiyani (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2018)
This research is a qualitative research aimed to describe management process in guiding teacher soft skill through halaqoh activity for PPA succession in SD al-Irsyad al-Islamiyyah Purwokerto. The results showed four findings. First, the planning of teacher's soft skill development through halaqoh activities is done by formulating halaqoh objectives, formulating teacher standardization, preparing halaqoh agenda, halaqoh officer schedule and halaqoh SOP. Second, the organizing of teacher's soft skill activities through halaqoh activities is done by assigning tasks to principals, musyrif and mu'allim. Third, the benefits gained from the implementation of this guidance activity is the quality and quantity of worship and the recitation of controlled teacher's Quran. It makes teacher soft skill renewable and has implications for the success of the Program of Morals Education for students. Fourth, controlling activities are carried out by the principal and mu'allim. The principal controls the presence of the teacher on halaqoh activities, while the mu'allim controls tahsin and tahfidz activities as well as the daily worship of the teacher.